Post-genomic views of a 'unique' metabolism in the eukaryotic flagellum. (26th October 2005) - Ginger, M.L.
Abstract : This short review summarizes recent advances in our understanding of energy metabolism within the eukaryotic flagellum. Using the example of adenylate kinase, we discuss how a requirement to target metabolic enzymes into the flagellum results in the presence of genes encoding novel isoforms of ubiquitous enzymes within flagellate eukaryotes.